How Beauty Works. Theoretical Mechanisms and Two Empirical Applications on Students’ Evaluation of Teaching - Wolbring, Tobias; Riordan, Patrick; et al. (Social Science Research, 2016)
Plenty of studies show that the physical appearance of a person affects a variety of outcomes in everyday life. However, due to an incomplete theoretical explication and empirical problems in disentangling different beauty effects, it is unclear which mechanisms are at work. To clarify how beauty works we present explanations from evolutionary theory and expectation states theory and show where both perspectives differ and where interlinkage appears promising. Using students' evaluations of teaching we find observational and experimental evidence for the different causal pathways of physical attractiveness. First, independent raters strongly agree over the physical attractiveness of a person. Second, attractive instructors receive better student ratings. Third, students attend classes of attractive instructors more frequently – even after controlling for teaching quality. Fourth, we find no evidence that attractiveness effects become stronger if rater and ratee are of the opposite sex. Finally, the beauty premium turns into a penalty if an attractive instructor falls short of students' expectation
Keywords: Physical attractiveness; Beauty premium; Beauty penalty; Evolutionary theory; Expectation states theory; Students' evaluations of teaching